Free N‐heterocyclic carbenes from Brønsted acidic ionic liquids: Direct detection by electrospray ionization mass spectrometry. (7th July 2022) - Salvitti, Chiara; Pepi, Federico; Managò, Marta; Bortolami, Martina; Michenzi, Cinzia; Chiarotto, Isabella; Troiani, Anna; de Petris, Giulia
Abstract : Rationale: The occurrence of N ‐heterocyclic carbenes in imidazolium‐based ionic liquids has long been discussed, but no spectroscopic evidence has been reported yet due to their transient nature. The insertion of an ionizable acid group into the cation scaffold of an ionic liquid which acts as a charge tag allows for the direct detection of free carbenes by mass spectrometry. Methods: Three different Brønsted acidic ionic liquids were synthesized: 1‐methyl‐3‐carboxymethylimidazolium chloride (MAICl), 1‐methyl‐3‐carboxymethylimidazolium acetate (MAIAc) and the corresponding 2‐(3‐methyl‐1 H ‐imidazol‐3‐ium‐1‐yl)acetate zwitterion (MAI − H). The speciation of these compounds was then analysed by electrospray ionization ion‐trap mass spectrometry in the negative ion mode. Results: The C2‐H deprotonation of the imidazolium cation leading to the formation of the corresponding carbene is highly affected by the basic properties of the counter‐anion. In the case of MAICl and MAI − H ionic liquids, no charged species corresponding to the free N ‐heterocyclic carbene was detected. On the contrary, in the presence of a sufficiently basic anion, such as acetate of MAIAc ionic liquid, an intense signal related to the free carbenic species was observed without the addition of an external base. Conclusions: In situ formation of free N ‐heterocyclic carbenes from Brønsted acidic ionic liquids was demonstrated, highlighting the crucial role of anion basicity in promoting the C2‐H proton abstraction from imidazolium cations with a carboxylic side chain.